2017
DOI: 10.3389/fncom.2017.00065
|View full text |Cite
|
Sign up to set email alerts
|

Size Matters: How Scaling Affects the Interaction between Grid and Border Cells

Abstract: Many hippocampal cell types are characterized by a progressive increase in scale along the dorsal-to-ventral axis, such as in the cases of head-direction, grid and place cells. Also located in the medial entorhinal cortex (MEC), border cells would be expected to benefit from such scale modulations. However, this phenomenon has not been experimentally observed. Grid cells in the MEC of mammals integrate velocity related signals to map the environment with characteristic hexagonal tessellation patterns. Due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…However, in doing so, this spiking implementation of grid cells increases the difficulty to integrate and test the interplay between multiple brain regions involved in spatial representation [34]. Indeed, one limitation of our model is the absence of spatially tuned signals contributing to grid-cell stabilization [12]. Similarly, in our simulations, the spiking activity grid cells was modulated by, but did not contribute to, the agents displacement in the environment.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, in doing so, this spiking implementation of grid cells increases the difficulty to integrate and test the interplay between multiple brain regions involved in spatial representation [34]. Indeed, one limitation of our model is the absence of spatially tuned signals contributing to grid-cell stabilization [12]. Similarly, in our simulations, the spiking activity grid cells was modulated by, but did not contribute to, the agents displacement in the environment.…”
Section: Discussionmentioning
confidence: 84%
“…Functionally, such a scale gradient has been suggested to operate as an accurate path-integration mechanism projecting to the DG and CA3 hippocampal sub-regions [10]. Moreover, the interaction between grid scales and other spatially tuned cells have been suggested to serve for minimizing errors in path integration [12].…”
Section: Introductionmentioning
confidence: 99%
“…Because hippocampal theta oscillatory components are known to be modulated by the locomotory speed in both rats (McFarland et al, 1975;Santos-Pata et al, 2017) and humans (Ekstrom et al, 2005), the higher theta (and lower gamma) amplitude observed in the early exploration phases could be a cofound of higher movement signals observed F I G U R E 3 Exploration phase modulates gamma activity and theta-gamma coupling A An example of raw LFP trace (black line) with highlighted segments of gamma (40-80Hz) bursting activity (red lines), computed using the dual amplitude threshold algorithm (see methods section). B BF gamma amplitude is higher (35.95+/-10.82 mean+/-std) at later compared to the early (33.05+/-10.50 mean+/-std) stages of exploration (related sample T-test; statistic=-4.38, p=0.007, effect size=-0.27).…”
Section: Resultsmentioning
confidence: 99%
“…A number of rodent and human studies investigating the functional role of hippocampal subregions support their distinct contributions to cognitive aspects such as spatial representations 31,32 , pattern separation in the dentate gyrus 33 , pattern completion in CA3 34 , temporal ordering in CA1 35 , memory retrieval in subiculum 36,37 and spatial decision-making 38,39 .…”
Section: Introductionmentioning
confidence: 99%